2016
DOI: 10.3109/13816810.2016.1164196
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in ACTG1 causing Baraitser-Winter syndrome with extremely variable expressivity in three generations

Abstract: Baraitser-Winter Syndrome (cerebro-frontofacial syndrome, type 3) is a rare developmental disorder typified by hypertelorism, ptosis, high arched eyebrows, ocular coloboma and brain malformations including lissencephaly. Other common manifestations include hearing loss, short stature, seizures, intellectual impairment and abnormalities of the kidney and urinary system. This syndrome is caused by missense mutations in the genes ACTB or ACTG1, both of which encode for cytoplasmic actin proteins crucial for prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…This change depends on regulated contraction of the actin-myosin cytoskeleton [163,164]. Mutations in the human cytoplasmic actin genes ACTG1 and ACTB have been implicated in Baraitser-Winter syndrome which includes ocular coloboma [70,165]. Studies in medaka fish have shown that basal constriction is achieved, at least partially, through the enrichment of focal adhesions at the basal ends of cells, and the resultant basolateral transmission of stress along the epithelial sheet.…”
Section: Invagination and Morphogenesis Of The Optic Cupmentioning
confidence: 99%
“…This change depends on regulated contraction of the actin-myosin cytoskeleton [163,164]. Mutations in the human cytoplasmic actin genes ACTG1 and ACTB have been implicated in Baraitser-Winter syndrome which includes ocular coloboma [70,165]. Studies in medaka fish have shown that basal constriction is achieved, at least partially, through the enrichment of focal adhesions at the basal ends of cells, and the resultant basolateral transmission of stress along the epithelial sheet.…”
Section: Invagination and Morphogenesis Of The Optic Cupmentioning
confidence: 99%
“…So the present patient is the third reported case of a BWCFF patient developing an hematological malignancy. At present, 52 molecularly confirmed BWCFF patients have been published [Gearing et al, ; Rivière et al, ; Johnston et al, ; Di Donato et al, , ; Eker et al, ; Poirier et al, ; Verloes et al, ; Kemerley et al, ]. Three individuals out of a total of 52 to have a haematologic malignancy is higher compared to the frequency of haematological malignancies in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Conditional γ-cytoplasmic actin knockout in the skeletal muscle results in progressive myopathy (Sonnemann et al, 2006) and affects muscle relaxation (O'Rourke et al, 2018). Seven different autosomal dominant missense mutations in the γ-actin gene have been linked to Baraitser-Winter syndrome (Kemerley et al, 2017) and progressive hearing loss in humans: T278I, T89I, K118M, P264L, P332A, I122V and V370A (Bryan et al, 2006;Liu et al, 2008;Rendtorff et al, 2006;van Wijk et al, 2003;Zhu et al, 2003). Together, these studies indicate an essential role for γ-actin in the maintenance of stereocilia, even though this actin isoform appears to be largely dispensable for the viability of an organism.…”
Section: Non-redundant Roles Of Actin Isoforms At the Organismal Levelmentioning
confidence: 93%
“…Two mutations in the human β-actin gene have been characterized: E364 K mutation, which has been correlated to neutrophil dysfunction (Nunoi et al, 1999), and R183W, linked to developmental malformations, dystonia and deafness (Procaccio et al, 2006). Human β-actin mutations, along with those in γ-cytoplasmic actin, have been linked to Baraitser-Winter syndrome (Kemerley et al, 2017). The severity of these mutations, as well as the lack of any observed homozygous mutations in the β-actin gene, present additional evidence of its highly essential biological role.…”
Section: Non-redundant Roles Of Actin Isoforms At the Organismal Levelmentioning
confidence: 99%